2018
DOI: 10.1080/2162402x.2018.1480286
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RON kinase potentiates anti-CTLA-4 immunotherapy to shrink breast tumors and prevent metastatic outgrowth

Abstract: The advent of immune checkpoint blockade as a new strategy for immunotherapy has changed the outlook for many aggressive cancers. Although complete tumor eradication is attainable in some cases, durable clinical responses are observed only in a small fraction of patients, underlining urgent need for improvement. We previously showed that RON, a receptor tyrosine kinase expressed in macrophages, suppresses antitumor immune responses, and facilitates progression and metastasis of breast cancer. Here, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 73 publications
3
24
0
Order By: Relevance
“…In this study, we found that MSP signaling via its receptor, RON, is critical for growth and proliferation of KB1P mammary cancer cells both in vitro and in vivo. These data accord well with previous publications in other mammary tumor models that rely on artificial, ectopic expression of MSP or the RON receptor (6,7,(9)(10)(11)(12)14). Most mechanistic work on the MSP-RON axis has used cell lines derived from the MMTV-PyMT model (6,9,12,14) that overexpress MSP, or genetically engineered mouse models in which Mst1r expression is driven by the MMTV promoter (7,11).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we found that MSP signaling via its receptor, RON, is critical for growth and proliferation of KB1P mammary cancer cells both in vitro and in vivo. These data accord well with previous publications in other mammary tumor models that rely on artificial, ectopic expression of MSP or the RON receptor (6,7,(9)(10)(11)(12)14). Most mechanistic work on the MSP-RON axis has used cell lines derived from the MMTV-PyMT model (6,9,12,14) that overexpress MSP, or genetically engineered mouse models in which Mst1r expression is driven by the MMTV promoter (7,11).…”
Section: Discussionsupporting
confidence: 87%
“…MSP and RON (over)-expression in breast cancer specimens correlates with poor prognosis and distant recurrence (5,6), suggesting that the MSP-RON axis contributes to disease progression. Indeed, experimental models, in which MSP or RON are overexpressed or the RON receptor is inhibited or genetically deleted, show that the MSP-RON axis drives mammary tumor progression and metastasis (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Recepteur D'origine Nantais or Ron Is A Receptor Tyrosine Kimentioning
confidence: 99%
“…In addition, Ruiz-Torres et al (48) demonstrated that the RON signaling pathway is associated with the immunosuppressive microenvironment in breast cancer. Ekiz et al (49) described that inhibition of RON kinase potentiates checkpoint immunotherapy in breast cancer. It is expected that the effectiveness of RON targeting anticancer therapy can be…”
Section: Ron Expression --------------------------------mentioning
confidence: 99%
“…CTLA-4 refers to an inhibitory molecule, which is expressed on the activated T cells, besides critically contributing to the balance existing between the pro-and anti-immune responses by downregulating the T cell signaling 23 . It has been reported that CTLA-4 overexpressed had a correlation with the poor prognosis in autoimmune diseases as well as the speci c kinds of cancer, including osteosarcoma and Ewing's sarcoma [24][25][26][27] ; however, the latent part played by CTLA-4 polymorphism in malignant bone tumors patients continue to be unclear. There are a number of research works that have investigated the correlation existing between the + 49G/A of the CTLA-4 gene and the susceptibility to malignant bone tumors, nevertheless, these results from published articles remained not just controversial but inconclusive as well.…”
Section: Discussionmentioning
confidence: 99%